(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate the early outcomes of laparoscopic cholecystectomy combined with common bile duct exploration and intraoperative choledochoscopy for choledocholithiasis at Phu Tho Provincial General Hospital. Methods: A cross-sectional descriptive study was conducted on 39 patients diagnosed with concomitant gallbladder stones and common bile duct stones. Results: From June 2022 to June 2025, a total of 39 patients underwent one-stage laparoscopic surgery at Phu Tho Provincial General Hospital. The conversion rate to open surgery was 5.2%, the stone clearance rate was 94.8%, and the postoperative complication rate was 7.7%, including one case (2.6%) requiring reoperation. No mortality was recorded. Conclusion: One-stage laparoscopic cholecystectomy combined with common bile duct exploration using intraoperative choledochoscopy is a feasible and safe procedure at the provincial hospital level. However, larger studies are needed to further validate its effectiveness.